Behavioral Aspect of Teenagers towards Internet Banking: An Empirical Study - D' Silva, Bernadette; D' Silva, Stephen; Bhuptai, Roshni Subodhkumar (Indian Journal of Marketing, 2010)
"Internet banking" refers to systems that enable bank customers to access accounts and general information on bank products and services through a personal computer (PC) or other intelligent device. Internet banking products and services can include wholesale products for corporate customers as well as retail and fiduciary products for consumers. Ultimately, the products and services obtained through Internet banking may mirror products and services offered through other bank delivery channels.